2006
DOI: 10.1073/pnas.0508997103
|View full text |Cite
|
Sign up to set email alerts
|

Cortistatin, an antiinflammatory peptide with therapeutic action in inflammatory bowel disease

Abstract: Cortistatin is a recently discovered cyclic neuropeptide related to somatostatin that has emerged as a potential endogenous antiinflammatory factor based on its production by, and binding to, immune cells. Crohn's disease is a chronic debilitating disease characterized by severe T helper 1 (Th1)-driven inflammation of the gastrointestinal tract. The aim of this study is to investigate the therapeutic effect of cortistatin in a murine model of colitis. Cortistatin treatment significantly ameliorated the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 33 publications
6
115
0
Order By: Relevance
“…CST is exerting its therapeutic effect on collagen induced arthritis partially through the ghrelin receptor, which can be partially reversed by a ghrelin-receptor antagonist (Gonzalez-Rey et al, 2007). In two other models studied by the group of Delgado, an experimental inflammatory bowel disease model and a sepsis model, treatment with CST demonstrates clinical and pathological amelioration of disease (Gonzalez-Rey et al, 2006a;Gonzalez-Rey et al, 2006b). These models show the downregulation of the Th1 response and the increase of regulatory T cells that are responsible for the recovery of the immune tolerance.…”
Section: Small-molecule Ghs Has a Considerable Immune-enhancing Effecmentioning
confidence: 99%
“…CST is exerting its therapeutic effect on collagen induced arthritis partially through the ghrelin receptor, which can be partially reversed by a ghrelin-receptor antagonist (Gonzalez-Rey et al, 2007). In two other models studied by the group of Delgado, an experimental inflammatory bowel disease model and a sepsis model, treatment with CST demonstrates clinical and pathological amelioration of disease (Gonzalez-Rey et al, 2006a;Gonzalez-Rey et al, 2006b). These models show the downregulation of the Th1 response and the increase of regulatory T cells that are responsible for the recovery of the immune tolerance.…”
Section: Small-molecule Ghs Has a Considerable Immune-enhancing Effecmentioning
confidence: 99%
“…In addition, cortistatin-14 was proposed recently as an alternative ligand for SRIF receptors in the immune system and as a new immunomodulatory factor with the capacity to deactivate the inflammatory response [19]. Recent studies reported a possible therapeutic action of cortistatin-14 in inflammatory bowel disease and septic shock, as assessed in murine models of colitis or endotoxemia [20,63].…”
Section: In Human Macrophagesmentioning
confidence: 99%
“…A total of 50 mg/ml colon tissue was homogenized and the MPO activity was measured as described previously (40). MPO activity was expressed as units per gram of tissue.…”
Section: Measurement Of Myeloperoxidase (Mpo) Activitymentioning
confidence: 99%
“…The detection limits are 15 pg/ml for IL-17, IL-6, IL-12p40, IL-4, IL-10, and IL-23, 30 pg/ml for IFN-␥ and IL-12p70, 7.8 pg/ml for IL-27p28, and 5 pg/ml for TNF. For measurement of tissue cytokines, colonic tissue was processed as previously described (40) and cytokine content was determined by ELISA.…”
Section: Cytokine Determination By Elisamentioning
confidence: 99%